Transformation of women at work in Asia an unfinished development agenda - Dasgupta, Sukti; Verick, Sher Singh 1973- (SAGE, 2016)
This book examines the drivers of, and barriers to, participation of women in the Asian labour market for its socio-economic development and structural transformation